2020
DOI: 10.1002/hlca.202000161
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐Supported Cationic Tungsten Imido Alkylidene Stabilized by an N‐Heterocyclic Carbene Ligand Boosts Activity and Selectivity in the Metathesis of α‐Olefins

Abstract: Dedicated to Prof. Antonio Togni for his contribution to coordination and fluorine chemistry A well-defined silica-supported cationic W imido alkylidene was prepared through surface organometallic chemistry. This catalyst shows preferential activity towards αover internal olefins, which is atypical for W-based catalysts, but consistent with the strong σ-donating ability of the NHC ancillary ligand. Complementing the studies on tungsten-based d 0 metathesis catalysts, the silica-supported cationic W imido alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…3d ). 121 Similarly, for the oxo systems replacement of the aryloxide ligand in [( SiO)W( O)( CH t Bu)(OHMT)] by a more σ-donating thiolate (SHMT) gives a substantially more active catalyst ( Fig. 3d ).…”
Section: Bridging the Gap Between Molecular And Supported Catalystsmentioning
confidence: 95%
“…3d ). 121 Similarly, for the oxo systems replacement of the aryloxide ligand in [( SiO)W( O)( CH t Bu)(OHMT)] by a more σ-donating thiolate (SHMT) gives a substantially more active catalyst ( Fig. 3d ).…”
Section: Bridging the Gap Between Molecular And Supported Catalystsmentioning
confidence: 95%
“…Metathesis from these systems initiates rapidly through cross‐metathesis of the starting alkylidene (usually a neopentylidene (R= t Bu), neophylidene (R=CMe 2 Ph) or, more recently, adamantylidene) and the olefin substrate [16–21] . These catalysts display very high turnover frequencies (TOFs) and turnover numbers (TONs) when the right ligand set is chosen, with often even higher activities upon immobilization on an oxide support [17,19,22,23] . Detailed studies have shown that, even with well‐defined high oxidation state alkylidenes, low valent Mo(IV) olefin complexes or dimeric compounds are generated during metathesis; [24,25] these have been shown to display poor albeit measurable activity.…”
Section: Introductionmentioning
confidence: 99%
“…Since its early mechanistic proposal, continuous efforts have been directed at gaining a detailed understanding of what makes specific metal alkylidenes good for this catalytic reaction . For instance, for early-transition-metal (d 0 ) metathesis catalysts that share a common structural motif(X)­(Y)­M­(CHR)­E (M = Mo or W, E = imido or oxo ligand, and X and Y are anionic ligands)each ligand has a tremendous influence on the stability of the reaction intermediates and the overall catalytic activity. , In that context, surface organometallic chemistry, , in combination with computational chemistry, has played a key role in the identification and understanding of the effect of each ligand . In particular, these studies, complemented by molecular chemistry, have shown that (i) the trigonal-bipyramidal (TBP) isomer is a key intermediate in the metathesis pathway while the square-pyramidal (SP) isomer is usually more stable and corresponds to an off-cycle intermediate and (ii) the anionic ligands play a major role in the stability of the TBP and SP metallacyclobutane intermediates and, in turn, drive the overall catalytic performance (Scheme A) .…”
Section: Introductionmentioning
confidence: 99%